THE EFFECT OF USING DIGIMON (SCIENCE DIGITAL MODULE) WITH SCIENTIFIC APPROACH AT THE VISUALIZATIONOF STUDENTS’ INDEPENDENCE AND LEARNING RESULTS - Syahroni, M. W.; Dewi, N. R.; Kasmui, K. (Jurnal Pendidikan IPA Indonesia, 2016)
The aim of this research was to determine the influence of digimon based scientific approach on independence and learning autcomes of learners. This research has designed as quasi-experimental nonequivalent control group design. Subjects of this reaserch is learners at 8 E and 8 F on SMP N 1 Magelang in year 2014/2015. The results showed that there was a strong perfect linear relationship between digimon with independent learning or learning outcomes of learners. The result of independent assessment on the experiment group was 85,47 while the result of independent assessment on the control group was 69,94. Digimon based scientific approach are influential 51.93% to the independence of learners, while the rest influenced by other factors. Digimon give influence 39.69% on learning outcomes of learners, while the rest influenced by other factors.This relation is empharized through an independent test (t-test) which shows dependent bridge between digimon with independence toward concept understanding of learners in experiment group.